The Beginnings of the Transformation of the Aesthetic Experience of Art at the Turn of the 20th and 21st Centuries - Liliana Kozak (Acta Universitatis Lodziensis: Folia Philosophica, 2025)
What is the experience of the digital revolution? We experience being in an expanded space of contact, AR and VR. The development of genetics, the possibility of interfering with the DNA of the organism has influenced works in the field of bio art. Man has excluded technological creations from the scope of nature, distinguishing part of his specificity as so different that he needs acceptance of his own activity. The experience of art is a certain shared manifestation of being, intersubjective, specific to man. Part of this experience is related to the specific time of creation and reception of a given creation. An attempt to capture the current change in experience, a certain atmosphere shared by the latest changes in art, using pioneering tools of science, is not only a possibility to answer the question about the current identity of the contemporary recipient, participant of the network. It is a search for a common direction of future works of art, technological inventions, imagining and building an environment that responds to the current need of art, to what kind of being we want to design for ourselves.